Effects of 16 Weeks of Cheerleading on Physical Self-Esteem and Mental Health of Female College Students - Deng, Chenliang; Yu, Qiaoyan; Luo, Ganglin; Lu, Shuiping (Frontiers in Psychology, 2022)
Objective: To study the influence of cheerleading on female college students' physical self-esteem and mental health. Methods: Sixty-three female college students in University of Electronic Science and Technology of China were trained in cheerleading for 16 weeks. The scores of each sub-field of physical self-esteem and psychological symptoms were analyzed by using Physical Self-Perception Profile (PSPP) and Symptom Checklist 90 (SCL-90) respectively at 0 and 16 weeks of experiment. Results: After 16 weeks of cheerleading exercise, female college students had significant differences in physical attractiveness (T =4.18), physical quality (T =4.39) and physical self-worth (T =3.35) before and after the experiment (P<0.01). There were significant differences in physical condition (T =3.87) and athletic ability (t=2.88) before and after the experiment (P<0.05). Somatization (T=6.485), obsessive-compulsive symptoms (T =11.716), interpersonal sensitivity (T =10.077), depression (T=8.403), anxiety (T=10.767), hostility (T=10.866), terror (T=9.260), paranoia (T=10.414), psychosis (T =9.610), sleep and eating disorders (T=9.323), total symptom index (T =13.245) and mean score of positive symptoms (T =12.237) were significantly different (P<0.01). Conclusion: Cheerleading can significantly improve the level of female college students' physical self-esteem, especially the self-esteem level of physical attractiveness, physical quality and physical self-worth. They also experienced significant improvement in their psychological disorders, especially somatization, depression, sleep and eating disorders, which effectively improved their overall mental health.